The Impact of the Past Conflict "Cumbok Tragedy" on Development Planning in Aceh - Teuku Kemal Fasya; Robert Sibarani; Budi Agustono; Muryanto Amin; Satia Negara Lubis; Herman Fithra (Proceedings of Malikussaleh International Conference on Multidisciplinary Studies (MICoMS), 2024)
The phenomenon of violence in the formation of nation-states in the 19th and 20th centuries, especially during the era of nationalism, had significant impacts on many countries, including Indonesia. This violence is linked to an official, exclusive, and elitist nationalism narrative, as seen in Aceh. The history of the "Cumbok Tragedy" in Aceh illustrates how nationalism can lead to violence. The impacts of conflict, such as in the Cumbok Tragedy, include infrastructure damage, security uncertainty, psychological effects, and social disruption. Development planning in East Aceh must consider rehabilitation, reintegration, and peace efforts to achieve effective and sustainable development. In the context of the Cumbok tragedy, the historical narrative that is written and often understood by the public originates from power and colonial control. Therefore, there is a need for a political movement to offer a new, more democratic, postcolonial meaning, bridging the sociocultural reconciliation movement. This research will be conducted in Aceh Regency, which is the epicenter of the conflict and the most distorted area in the history of the Cumbok Tragedy. A qualitative social approach with a case study method will be used to explore the real-life situation of the case. The research results on the Cumbok Tragedy in East Aceh reveal the complexity of history through in-depth narratives from the families of the victims, such as Teuku Saiful Anwar and Cut Anzar Hanum, who highlight the direct impacts and differing perspectives compared to the official historical version. The inaccuracies in the current historical writing have caused tensions, underscoring the importance of historical reconciliation. Experts, including Prof. Ismail Fahmi Arrauf Nasution, emphasize that honest and balanced disclosure, along with university involvement, is a crucial step to improving historical understanding and building sustainable peace in Aceh. Awareness of various perspectives and a commitment to reconciliation are key to healing past wounds and creating a more harmonious future.